Advanced mandibular reconstruction with fibular free flap and alloplastic TMJ prosthesis with digital planning - Justin M. Pyne; Clayton M. Davis; Ryan Kelm; Claudine Bussolaro; Walter Dobrovolsky; Hadi Seikaly (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Introduction Resection of the mandible and temporomandibular joint (TMJ) without formal reconstruction is a devastating condition that negatively affects all aspects of the patient’s life. We have approached the reconstruction of mandibular defects that include the condyle with simultaneous reconstruction with a vascularized free fibular flap (FFF) using Surgical Design and Simulation (SDS) and alloplastic TMJ prosthesis. The objective of this study is to report the functional and quality of life (QOL) outcomes in a cohort of patients that had undergone our reconstructive protocol. Methods This was a prospective case series of adult patients that underwent mandibular reconstruction with FFF and alloplastic TMJ prosthesis at the our center. Pre-operative and post-operative maximum inter-incisal opening (MIO) measurements were collected, and patients completed a QOL questionnaire (EORTC QLQ—H&N35) during those perioperative visits. Results Six patients were included in the study. The median patient age was 53 years. Heat map analysis of the QOL questionnaire revealed that patients reported a positive clinically significant change in the domains of pain, teeth, mouth opening, dry mouth, sticky saliva, and senses (relative change of 2.0, 3.3, 3.3, 2.0, 2.0, and 1.0 respectively). There were no negative clinically significant changes. There was a median perioperative MIO increase of 15.0 mm, and this was statistically significant (p  =  0.027). Conclusions This study highlights the complexities involved in mandibular reconstruction with involvement of the TMJ. Based on our findings, patients can obtain an acceptable QOL and good function following simultaneous reconstruction with FFF employing SDS and an alloplastic TMJ prosthesis. Graphical Abstract